(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
The peculiarities of the anatomical structure of the one-year stem D. virginiana are analyzed and revealed. It is characterized by a subepidermal peredermum with rounded lentils raised over the covering tissues. They are placed by a continuous ring along the axis of the stem lamellar parenchyma with the domination of scleralenchymal fibers in the perimedular zone. Its characterized by the absence of clearly pronounced triangular regions of the heart rays in the secondary phloem. Well-developed mechanical tissues (lumbar cranial hips, pericyclical sclerenchyma, bast fibers, fibroids, libriform) are present in all areas of the stem. Stocking parenchyma of the primary cortex, phloem, xylem, and the core rays of the peripheral and middle parts of the core are key characteristic of anatomical structure. The distribution of mechanical and parenchymal tissues makes it possible to characterize the anatomical structure as mesoxerophytic.